lncRNA SNHG3 acts as a novel Tumor Suppressor and regulates Tumor Proliferation and Metastasis via AKT/mTOR/ERK pathway in Papillary Thyroid Carcinoma - Duan, Yu (J Cancer, 2020)
The incidence of papillary thyroid carcinoma (PTC) has been increased rapidly in recent decades. Long noncoding RNAs (lncRNA) are a class of non-protein-coding transcripts and play critical roles in regulating gene expression and influence biological behaviors of multiple cancers, including PTC. Here, we discovered that lncRNA SNHG3 was significantly downregulated in PTC tissues and cell lines, the expression of SNHG3 was negatively correlated with the TNM stage and poor prognosis of PTC patients. Functional studies illustrated that the depletion of SNHG3 via CRISPR/Cas9 technology promoted the proliferation, migration and invasion abilities of PTC cells. Tumor xenograft models confirmed the tumor-promoting role of silenced SNHG3 in vivo. Further mechanistic analyses revealed that knockout of SNHG3 activated the AKT/mTOR/ERK pathway in PTC cell lines and the mTOR inhibitor AZD8055 abrogated the tumor-promoting effect induced by SNHG3 inhibition. Taken together, our findings identified a lncRNA SNHG3 that functions its tumor-suppressor role during PTC development and SNHG3 might serve as a promising candidate for target therapy of PTC.